(untitled) (Journal of the College of Basic Education, 2024)
The supreme religious authority in Najaf, represented by the Grand Ayatollah Ali al-Sistani, insisted on political resistance using the same weapon that the occupier came with, which is to spread democracy. Writing the constitution, or appointing the government, and insisted from the beginning that everything emanates from the popular will and through the mechanism of general elections, despite the difficult circumstances that Iraq was going through at the time, and it entered into a fierce struggle with the coalition authority until it was finally able to force it to come down at its will The vast majority of the Iraqi people. Al-Sistani insisted on the elections for principled reasons, the most important of which is not to give any room for dictatorship and authoritarianism. Therefore, he believed in the elections as the best way to enable the Iraqi people to form a government that takes care of their interests. The religious authority believes that its role means supervising the spiritual, worship and social affairs of the believers, and it is an assignment and not an honor, and it is above all a social religious position and not a political center. Therefore, in the opinion of the religious authority, elections are not only a political matter, but rather a social matter, and the social matter is included in the circle of concerns The reference, and by virtue of Mr. Sistani’s perception of the position of the religious authority, he considers himself obligated to deal with the issue of elections, which he believes is the solid foundation for the political process and social life in any society or country.